Leaf anatomy and dereplication by FIA-ESI-IT-MS/MS of secondary metabolites of Clusia criuva Cambess as an integrative approach to assess the environmental status of coastal plain forests - de Souza Mesquita, Leonardo M. [UNESP]; Pereira, Vinícius Filipe Fernandes [UNESP]; Nunes, Beatriz Zachello; Ragagnin, Marilia Nagata; Pereira Tangerina, Marcelo M.; da Rocha, Cláudia Quintino; de Almeida, Odair José Garcia [UNESP]; Martins, Maria Bernadete Gonçalves [UNESP]; Vilegas, Wagner [UNESP] (Springer Nature, 2023)
The increasing development of industry, ports, tourism, and commerce along the coasts poses a severe threat to local forests due to elevated levels of pollutants. An effective way to assess the impact of this contamination is by evaluating living organisms' anatomical features and chemical composition. This research examined the potential of Clusia criuva Cambess leaves as a bioindicator model for screening sandy coastal plain forests (Restingas). The study collected samples from pristine (PA) and disturbed (DA) areas, confirmed through literature review and sediment concentration by guidelines analysis. Microscopy images of the leaves revealed that PA samples are thicker and have fewer druse crystals than DA. Mass spectrometry fingerprint analysis identified key compounds such as flavonoids, benzophenones, and phenolic acids (FIA-ESI-IT-MS/MS), which could be considered chemical markers from the genus. The chemical composition of extracts from PA and DA differed significantly, with a low similarity index (40%). Quinic acid derivatives are found only in plants from PA, which may be a response against intense herbivory agents. Instead, 7-epi-nemerosone, was detected only samples from DA, probably due to the need to defend against oxidative stressors. Besides, the similarity between each study area's three distinct sampling points was around 80%, indicating low chemical variability within the exact location. This study demonstrates an integrative methodology for assessing and supporting the environmental status of Restinga ecosystems, ensuring a comprehensive response that can promote conservation strategies.
Keywords: Clusia criuva Cambess; Coastal plain forests; Environmental monitoring; Leaf anatomy; Secondary metabolites